Facing Divorce with Family Resilience: Challenges and Post-Mediation Solutions in the Panyabungan Religious Court - Muhamad Hasan Sebyar; Nur Azizah (Madania: Jurnal Kajian Keislaman, 2024)
Divorce is a growing social phenomenon in Indonesia and has a negative impact not only on the couple concerned, but also on children and society. One of the efforts to prevent divorce is through mediation, where couples are facilitated to resolve conflicts without having to go through a lengthy process. However, despite the success of mediation, challenges in maintaining family resilience after mediation remain. This study aims to identify the factors that affect family resilience after mediation and strategies that can be applied to strengthen the couple's relationship after mediation. This research is an empirical legal research, using a legal sociology approach. Data were collected through in-depth interviews with couples who had gone through the mediation process in divorce cases, participatory observation, and document analysis. The analysis was carried out by thematic coding to identify factors that affect family resilience. The results show that family resilience after mediation is influenced by factors such as effective communication, restoration of trust, loyalty and commitment, as well as support from extended family. In addition, some strategies that can be applied to strengthen family resilience are post-mediation counseling, communication skills development, mentoring from third parties, and social support. Although mediation has succeeded in stopping divorce, couples still need to work hard to maintain their family's resilience by implementing the right strategies. Support from external parties and strong commitment from the spouse are essential to maintain harmony in the future household. Perceraian adalah fenomena sosial yang semakin meningkat di Indonesia dan berdampak negatif tidak hanya pada pasangan yang bersangkutan, tetapi juga pada anak-anak dan masyarakat. Salah satu upaya untuk mencegah perceraian adalah melalui mediasi, di mana pasangan difasilitasi untuk menyelesaikan konflik tanpa harus melalui proses yang panjang. Namun, meskipun mediasi berhasil, tantangan dalam mempertahankan ketahanan keluarga pasca mediasi tetap ada. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi ketahanan keluarga pasca mediasi dan strategi yang dapat diterapkan untuk memperkuat hubungan pasangan setelah mediasi. Penelitian ini merupakan penelitian hukum empiris, dengan menggunakan pendekatan sosiologi hukum. Data dikumpulkan melalui wawancara mendalam dengan pasangan yang telah melalui proses mediasi dalam kasus perceraian, observasi partisipatif, serta analisis dokumen. Analisis dilakukan dengan pengkodean tematik untuk mengidentifikasi faktor-faktor yang mempengaruhi ketahanan keluarga. Hasil penelitian menunjukkan bahwa ketahanan keluarga pasca mediasi dipengaruhi oleh faktor-faktor seperti komunikasi efektif, pemulihan kepercayaan, kesetiaan dan komitmen, serta dukungan dari keluarga besar. Selain itu, beberapa strategi yang dapat diterapkan untuk menguatkan ketahanan keluarga adalah konseling pasca mediasi, pengembangan keterampilan komunikasi, pendampingan dari pihak ketiga, dan dukungan sosial. Meskipun mediasi berhasil menghentikan perceraian, pasangan masih perlu bekerja keras untuk mempertahankan ketahanan keluarga mereka dengan menerapkan strategi-strategi yang tepat. Dukungan dari pihak eksternal dan komitmen yang kuat dari pasangan sangat penting untuk menjaga harmoni rumah tangga di masa depan.